Spatial characteristics of population ageing in Slovenia: a comparative analysis of proportion of the elderly in the period 1981–2013 by administrative units - Kerbler, Boštjan (Journal for Geography, 2013)
Slovenian population is characterized by an accelerated ageing. This article proceeds from the assumption that this process is not uniformed in Slovenia and that there are different areas of ageing. The analysis focused on the period 1981–2013, since the ageing of the population in Slovenia has been intensified. Results confirmed our assumption and determined four areas of ageing as a result of various forms of migrations of the Slovenian population. In conclusion, the guidelines for further research of the dynamics of ageing in Slovenia are stated.